2019
DOI: 10.4018/978-1-5225-4200-1.ch005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Sharing and Innovative Work Behavior

Abstract: The growing importance of knowledge sharing is promoting individual innovative work behavior (IWB) to create new products or services for innovative business systems. Also, the key challenges faced by individuals in their knowledge sharing behavior (KSB) are personal perceptions and environmental influences. Thus, this chapter provides a research model using an extension of social cognitive theory that comprises environmental factors (subjective norms, trust), personal factors (knowledge self-efficacy, enjoyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The results showed that knowledge sharing has a positive effect on innovative work behavior in the Regional Revenue Agency of West Java Province. The results of this study support the results of Phung et al (2017;; Akram et al (2018); Hasan et al (2018), Khorakian et al (2019), andKmieciak, R. (2020).…”
Section: Hypothesis Testingsupporting
confidence: 92%
“…The results showed that knowledge sharing has a positive effect on innovative work behavior in the Regional Revenue Agency of West Java Province. The results of this study support the results of Phung et al (2017;; Akram et al (2018); Hasan et al (2018), Khorakian et al (2019), andKmieciak, R. (2020).…”
Section: Hypothesis Testingsupporting
confidence: 92%
“…Researchers have well established the importance of innovative work behavior (IWB) in the context of organizational workplace setting. IWB refers to the intentional introduction and implementation of novel ideas in order to suggest new solutions to existing problems, to improve products/services, and to proactively explore new opportunities (De Jong & Den Hartog, 2010;Dong & Hawryszkiewycz, 2019). In order to align their business models in accordance with the current market needs, organizations need to foster and adopt innovative solutions and creative ideas (Javed et al, 2017).…”
Section: Palabras Clavementioning
confidence: 99%
“…Knowledge is regarded as the most valuable asset of an organization, because it contributes to individual and organizational success. Dong and Hawryszkiewycz (2019) stresses the growing importance of knowledge sharing among individuals of an organization, which in turn, enhances the innovative potential of its employees, thus resulting in increased knowledge creation and innovative potential. Knowledge sharing is a cyclical process in which individuals internalize shared knowledge and then transfer it to others through externalization (Shujahat et al, 2019).…”
Section: Palabras Clavementioning
confidence: 99%